Kompleks Ratu Boko: Latar Belakang Pemilihan Tempat Pembangunannya - nfn. Kusen (Berkala Arkeologi, 1995)
During his involvement in the preparation of the 1992 Boko Regional Tourism Development Foundation Plan and the 1994/1995 Ratu Boko Area Development Feasibility Study, the author has collected and analyzed various historical-archaeological data on the Ratu Boko site. In this short paper, it is impossible to describe everything that is described in the two activity reports. Therefore, what will be presented is limited to a summary of the results of the analysis and its interpretation.